THU0004 Cross phenotype association mapping of the mhc identifies genetic variants that differentiate psoriatic arthritis from psoriasis. (15th June 2017) - Bowes, J; Ashcroft, J; Dand, N; Ho, P; Smith, CH; Barker, JN; McHugh, N; Warren, RB; Barton, A; ,
Abstract : Background: The identification of genetic variants that differentiate PsA from psoriasis has the potential to help us understand the underlying biological pathways that lead to the development of PsA. Associations to genetic variants within the major histocompatibility complex (MHC), in particular to HLA-C*0602, increase risk of both PsA and psoriasis when compared to control populations. However direct comparisons of PsA to psoriasis have led to paradoxical associations where HLA-C*0602 has been reported to be protective of PsA. In addition HLA-C*0602 has been reported to be associated with age of onset of psoriasis. A more recent study has reported the amino acid at position 45 of the HLA-B protein as the most important factor for differentiating PsA from psoriasis. Objectives: Here we perform a cross phenotype association analysis in an attempt to identify genetic variants in the MHC that differentiate PsA from psoriasis in a large collection of PsA patients and psoriasis patients screened for the absence of PsA. Methods: A total of 1069 patients with psoriasis and 981 patients with PsA from the UK were genotyped using either the Illumina Immunochip or the Illumina OmniExpress genotyping arrays. SNPs, amino acids and classical HLA alleles were imputed using SNP2HLA. Logistic regression was used to compare the imputed dosage of MHC markers between PsA and psoriasis. All analyses were repeated using age of psoriasis onset as an additional covariate. Results: The most significant association when comparing PsA to psoriasis was to HLA-C*0602 (p=4.17x10 -15 ) with a protective effect for PsA (OR 0.52, CI 0.44:0.61). HLA-C*0602 was found to be significantly associated with a younger age of psoriasis onset (p=1.51x10 -60 ) where the median age of onset in years for carriage is 22 compared to 33 for non-carriage. We observed a difference in the median age of psoriasis onset in years between the PsA and psoriasis study subgroups (34 vs. 21), highlighting the potential for bias at markers associated with age of psoriasis onset. When controlling for the age of psoriasis onset in the analyses we observed no association of PsA to HLA-C*0602 (p=0.07) and the most significant association was to the amino acid at position 97 of HLA-B (p=1.54x10 -9 ) where the presence of asparagine or serine residue increased risk of PsA. Asparagine at position 97 of HLA-B defines the HLA-B*2705 allele. Conclusions: Comparing PsA to psoriasis we show HLA-C*0602 confers no effect, either risk or protective, for PsA after correction for age of psoriasis onset. The results suggest that the previously observed protective effect of HLA-C*0602 could be due to confounding due to a younger age of psoriasis onset in the psoriasis subgroup. When accounting for age of psoriasis onset, the primary association conferring risk for PsA in patients with psoriasis is to HLA-B amino-acid 97 where an asparagine residue defines the HLA-B*2705 allele. In addition, this amino acid has been reported as the largest genetic effect for ankylosing spondylitis thereby refining the genetic overlap between these two spondyloarthropathies. Disclosure of Interest: None declared